2013
DOI: 10.3386/w19047
|View full text |Cite
|
Sign up to set email alerts
|

Post-recession US Employment through the Lens of a Non-linear Okun's law

Abstract: This paper aims at investigating the relationship between employment and GDP in the United States. We disentangle trend and cyclical employment components by estimating a non-linear Okun's law based on a smooth transition error-correction model that simultaneously accounts for long-term relationships between growth and employment and short-run instability over the business cycle. Our findings based on out-of-sample conditional forecasts show that, since the exit of the 2008-09 recession, US employment is on av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…6. Relationship between unemployment and growth in Okun law in the sort run and long run had been studied by Shin et al (2014) and Chinn et al (2013), and they found ( by using cointegration models) that the short and long run dynamics could be unequal. However, Knotek (2007) found a substantial variation in the relation between unemployment rate and real GDP growth in the short run, that is, he found that there is not always a negative relationship between unemployment and output growth in the short run.…”
Section: Summary Of Some Empirical Studiesmentioning
confidence: 99%
“…6. Relationship between unemployment and growth in Okun law in the sort run and long run had been studied by Shin et al (2014) and Chinn et al (2013), and they found ( by using cointegration models) that the short and long run dynamics could be unequal. However, Knotek (2007) found a substantial variation in the relation between unemployment rate and real GDP growth in the short run, that is, he found that there is not always a negative relationship between unemployment and output growth in the short run.…”
Section: Summary Of Some Empirical Studiesmentioning
confidence: 99%
“…Cheng et al (2015) also provide evidence of steepening of the coefficient using non-parametric Bayesian techniques. Chinn et al (2013) apply a sophisticated non-linear econometric model (a smooth transition error-correction model) to log-changes in US employment and GDP. Their results point to a jobless recovery, in contrast to the results of Ball et al (2013), with cyclical factors unable to account for around a quarter of total job losses.…”
Section: Recent Workmentioning
confidence: 99%
“…For example, Shin et al (2014), proposed the NARDL in which the short and long run dynamics could be asymmetric. Chinn et al (2013), presented a smooth transition VECM with a unique long run relationship but the short run dynamics and the speed of adjustment varied over expansions and recessions. The threshold cointegration model (TVECM) that is similar to the smooth transition VECM, has been introduced by Balke and Fomby (1997).…”
Section: Introductionmentioning
confidence: 99%